Edukasi Sampah Laut dan Dampaknya terhadap Kehidupan Organisme Laut bagi Siswa SMP Kristen Rehoboth - Milyan Uli Latue; Juliana Wilmiena Tuahatu; Frijona Fabiola Lokollo; Valentine Domaris Saleky; Fahrul Rozy Fakaubun; Ronald Darly Hukubun (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service activity aims to improve the understanding of Rehoboth Christian Middle School students in Ambon regarding marine debris, its sources, and its impact on marine organisms through an interactive educational approach. Ambon Bay, as a semi-enclosed body of water, faces a serious problem in the form of accumulated plastic waste, most of which originates from land-based activities. The activity was carried out through a presentation-based socialization, pre-test, discussion, and post-test. The evaluation results showed a significant increase in three main aspects: understanding marine debris, waste sources, and how to reduce it, from 53–63% in the pre-test to 100% in the post-test. The material provided emphasized the local context of Ambon Bay, including waste sources, its ecological impact on biota, and prevention efforts in the school environment. This activity succeeded in raising ecological awareness and encouraging concrete actions such as sorting waste, reducing single-use plastics, and maintaining a clean environment. This program has proven effective in fostering environmental awareness from an early age.